Comparison of Outcomes and Complications of Isolated Acetabular Fractures and Acetabular Fractures With Associated Injuries. Issue 1 (January 2017) - Phruetthiphat, Ong-art; Willey, Michael; Karam, Matthew D.; Gao, Yubo; Westerlind, Brian O.; Marsh, J. Lawrence
Abstract : Objective: To compare patients with acetabular fractures that are isolated (acetabular fracture alone) and acetabular fracture presenting with additional nonacetabular injury using functional outcomes, complications, and readmissions. Design: Retrospective review. Setting: Level 1 Trauma Center. Patients/Participants: Two hundred fifteen patients underwent open surgical treatment for acetabular fracture between 2003 and 2012 with age ≥18 years and minimum 1-year follow-up inclusive of functional scores and complications. Intervention: Surgical treatment of acetabular fracture. Main Outcome Measurements: Postoperative functional outcomes at 1 year as assessed with the Short Form 36 (SF-36) Health Survey Questionnaire and the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), postoperative complications including readmissions. Results: Acetabular fractures patients with associated nonacetabular injuries exhibited a longer length of hospital stay ( P < 0.0001) and higher readmission rate within 90 days ( P = 0.012) compared with patients in the isolated injury group. Acetabular fracture with either chest or abdominal injury had the longest average hospital stay (19.2 and 19.1 days, respectively). Functional scores between 2 groups were comparable at 1-year follow-up, except acetabular fractures with pelvic ring injury, which had a significantly lower physical component score of SF-36 ( P = 0.007) compared with the isolated group. Conclusions: Acetabular fractures with associated nonacetabular injuries have longer hospital stays, higher complications, and readmissions. Specifically, patients with associated truncal injury had worse clinical outcome and longer hospital stays. These conclusions should be taken into account when counseling patients with acetabular fractures, as additional injuries will greatly affect the course of treatment and the outcomes. Level of Evidence: Prognostic level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.